2018
DOI: 10.1016/j.jvs.2018.02.035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statin use and intensity on stroke and myocardial infarction after carotid endarterectomy

Abstract: Objective: Statin use in patients with cerebrovascular disease undergoing carotid endarterectomy (CEA) has been advocated for prevention of stroke and cardiovascular events. However, the effect of statin therapy on long-term outcomes after CEA still needs to be delineated. Methods: OptumLabs Data Warehouse, a comprehensive, longitudinal, real-world dataset with deidentified lives across claims and clinical information, was used to analyze the rates of stroke, myocardial infarction (MI), and statin use after CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…NR NR Tung et al (2017) [ 60 ] Taiwan National Health Research Insurance database from 2009 to 2012 AMI, UA, stroke, resuscitation after cardiac arrest, all cause death, cardiac revascularization procedure AMI: 410–410.9; UA: 411.1; stroke: 430–437; resuscitation after cardiac arrest: 427.5; revascularization: 36.0–36.03, 36.05–36.09, 36.1–36.99, V45.81 (ICD-9). NR NR Arinze et al (2018) [ 61 ] OptumLabs Data Warehouse from 2004 to 2014 AMI, stroke AMI: 410; stroke: 434, 434.0, 434.00, 434.01, 434.1, 434.10, 434.11, 434.9, 434.90, 434.91 (ICD-9). NR NR Baviera et al (2018) [ 62 ] Administrative health databases of Lombardy from 2002 to 2014 ACS, stroke, all cause death, major amputation ACS: 410.xx, 411; stroke: 430, 431, 434.xx, 436, 433.11; major amputation: 84.10, 84.13, 84.14, 84.15, 84.16, 84.17, 84.18, 84.19 (ICD-9).…”
Section: Resultsmentioning
confidence: 99%
“…NR NR Tung et al (2017) [ 60 ] Taiwan National Health Research Insurance database from 2009 to 2012 AMI, UA, stroke, resuscitation after cardiac arrest, all cause death, cardiac revascularization procedure AMI: 410–410.9; UA: 411.1; stroke: 430–437; resuscitation after cardiac arrest: 427.5; revascularization: 36.0–36.03, 36.05–36.09, 36.1–36.99, V45.81 (ICD-9). NR NR Arinze et al (2018) [ 61 ] OptumLabs Data Warehouse from 2004 to 2014 AMI, stroke AMI: 410; stroke: 434, 434.0, 434.00, 434.01, 434.1, 434.10, 434.11, 434.9, 434.90, 434.91 (ICD-9). NR NR Baviera et al (2018) [ 62 ] Administrative health databases of Lombardy from 2002 to 2014 ACS, stroke, all cause death, major amputation ACS: 410.xx, 411; stroke: 430, 431, 434.xx, 436, 433.11; major amputation: 84.10, 84.13, 84.14, 84.15, 84.16, 84.17, 84.18, 84.19 (ICD-9).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Arinize et al demonstrated in 21,277 patients who underwent CEA from 2004 to 2014 that postoperative statin use was associated with lower perioperative stroke at 30 and 90 days (OR .77 [.61-.98]; OR .75 [.62-.90]). 22 Statin use was also shown to independently protect against long-term stroke (HR .82 [.75-.91]) and MI (HR .83 [.75-.92]). Our study shows a significant change in statin use over time, with the earliest era not prescribing statins postoperatively in 50.6% of cases while the current era does not prescribe only 10.0% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a noticeable improvement in medical treatment for carotid stenosis, including the use of statins, in the last 20 years. [ 33 ] Additionally, the CEA procedure is more likely to be centralized in high-volume vascular centers with experienced surgeons. [ 34 ] Moreover, due to the development of CAS, CAS could be an alternative for some patients who are considered high risk for undergoing CEA.…”
Section: Discussionmentioning
confidence: 99%